How much is too much? A case report of nutritional supplement use of a high-performance athlete - Carlsohn, A.; Cassel, M.; Linne, K.; Mayer, F. (British Journal of Nutrition, 2011)
Although dietary nutrient intake is often adequate, nutritional supplement use is common among elite athletes. However, high-dose supplements or the use of multiple supplements may exceed the recommended daily allowance (RDA) of particular nutrients or even result in a daily intake above tolerable upper limits (UL). The present case report presents nutritional intake data and supplement use of a highly trained male swimmer competing at international level. Habitual energy and micronutrient intake were analysed by 3 d dietary reports. Supplement use and dosage were assessed, and total amount of nutrient supply was calculated. Micronutrient intake was evaluated based on RDA and UL as presented by the European Scientific Committee on Food, and maximum permitted levels in supplements (MPL) are given. The athlete`s diet provided adequate micronutrient content well above RDA except for vitamin D. Simultaneous use of ten different supplements was reported, resulting in excess intake above tolerable UL for folate, vitamin E and Zn. Additionally, daily supplement dosage was considerably above MPL for nine micronutrients consumed as artificial products. Risks and possible side effects of exceeding UL by the athlete are discussed. Athletes with high energy intake may be at risk of exceeding UL of particular nutrients if multiple supplements are added. Therefore, dietary counselling of athletes should include assessment of habitual diet and nutritional supplement intake. Educating athletes to balance their diets instead of taking supplements might be prudent to prevent health risks that may occur with long-term excess nutrient intake.